Private Solutions for Infrastructure in Rwanda : A Country Framework Report - Private-Public Infrastructure Advisory Facility (Washington, DC: World Bank, 2013)
This report aims to provide an objective assessment of the condition of Rwanda's infrastructure sectors and of the institutional and policy frameworks that are associated with them. It also provides a clear route map for infrastructure sector reform, as well as highlighting both the opportunities that exist for the private sector and the role that the donor community can play in assisting the Government with establishing priorities in infrastructure.